Distribution of Corynebacterium Species and Comparative Results of Diagnostic Methods for Identifying Corynebacterium in Experimental Mice in Korea - Sehee Park; Hijo Shin; Sangwoon Kim; Teakchang Lee; Haejin Lee; Kihoan Nam; Wonkee Yoon; Hyoungchin Kim; Youngwon Seo; Youngsuk Won; Hyojung Kwon (Veterinary Sciences, 2022)
The genus Corynebacterium, composed of Gram-positive diphtheroid rod-shaped bacteria, induces severe diseases, such as Corynebacterium-associated hyperkeratosis and pseudotuberculosis, in immunodeficient mice. We isolated and identified a total of 165 strains of Corynebacterium species from experimental mice in Korean laboratories, diagnosed using several methods. When identified based on molecular methods, namely, 16S rRNA and rpoB gene sequence analysis, the main Corynebacterium species isolated in Korean laboratory mice were C. mastitidis (44.8%, n = 74), C. bovis (25.5%, n = 42), C. lowii (21.2%, n = 35), and C. amycolatum (8.5%, n = 14). Diagnoses were also performed using matrix-assisted laser desorption/ionization–time of flight mass spectrometry (MALDI-TOF MS) and biochemical methods. MALDI-TOF MS yielded results that were 77.9% identical to the molecular identification results, whereas biochemical methods showed only 15.5% identical to molecular identification, partly owing to difficulties in distinguishing among C. mastitidis strains. Collectively, our findings indicate that molecular biological methods are better suited for detecting and identifying Corynebacterium species candidates isolated from mice than biochemical methods. Because of limitations associated with the use of MALDI-TOF MS, more precise results will be obtained by complementing this approach with other methods when used for rapid identification testing.